Evaluating the impact of maternal dietary vitamin D supplementation on sow performance, serum 25OHD3, and subsequent pig performance - Flohr, J. R.; Bergstrom, J. R.; Woodworth, Jason C.; Tokach, Michael D.; DeRouchey, Joel M.; Dritz, Steven S.; Goodband, Robert D. (My University, 2016)
A total of 104 sows (PIC 1050; mean parity 2.2 ± 0.3) in 4 farrowing groups (25–27 sows per group) were used to determine the effects of gestational and lactational vitamin D supplementation on sow performance and serum 25OHD3. Sows were allotted to 1 of 4 dietary treatments (800, 2000, or 9600 IU of D3, or 50 µg of 25OHD3 [equivalent to 2000 IU/kg D3, DSM Nutritional Products Inc., Parsippany, NJ] per kg of diet) in a CRD. There were 25 to 27 sows per treatment. Maternal performance was not impacted by treatments. Increasing dietary D3 increased (linear, P = 0.001) sow serum 25OHD3. Sows fed 50 µg/kg of 25OHD3 had greater (P < 0.001) serum 25OHD3 than sows fed 800 or 2000 IU/kg, but decreased (P < 0.004) serum 25OHD3 compared to sows fed 9600 IU/kg. At weaning, increased maternal D3 increased piglet serum 25OHD3 (quadratic, P = 0.033), and pigs from sows fed 50 µg/kg of 25OHD3 had greater (P = 0.001) serum 25OHD3 compared to pigs from sows fed 800 IU/kg D3, but lower (P = 0.001) than pigs from sows fed 9600 IU/kg of D3. A subsample population of pigs (n = 448; PIC 327 × 1050; initially 6.6 ± 0.3 kg; 21 d of age) from 52 litters (2 of 4 farrowing groups) were used in a split-plot design (maternal treatment = whole plot; nursery treatment = subplot) to determine the influence of maternal and nursery dietary vitamin D on postweaning growth. Once weaned, pigs were allotted to pens based on maternal treatment, maintaining pre-weaning BW differences, and pens were randomly assigned to 2 nursery diets (2000 IU D3/kg or 50 µg 25OHD3/kg). There were 12 and 9 pens/treatment in nursery and finishing, respectively. Pen was the experimental unit. Growth performance was not influenced by nursery vitamin D. In the nursery, pigs from sows fed increasing D3 had increased (quadratic, P < 0.003) ADG and ADFI. Throughout finishing, ADG and G:F increased (quadratic, P < 0.05) with increasing maternal D3. Pigs from sows fed 50 µg/kg 25OHD3 had increased (P = 0.002) ADG compared to pigs from sows fed 800 IU/kg D3. Overall, increasing maternal D3 increased serum 25OHD3 concentrations, but more D3 (on an equivalent IU basis) is needed to achieve similar serum 25OHD3 responses compared to feeding 25OHD3. Pigs from sows fed 2000 IU/kg D3 grew faster after weaning compared to pigs from sows fed 800 or 9600 IU/kg D3 and pigs from sows fed 25OHD3 had greater ADG compared to pigs from sows fed 800 IU/kg D3.
Citation: Flohr, J. R., Bergstrom, J. R., Woodworth, J. C., Tokach, M. D., DeRouchey, J. M., Dritz, S. S., & Goodband, R. D. (2016). Evaluating the impact of maternal dietary vitamin D supplementation on sow performance, serum 25OHD3, and subsequent pig performance. Journal of Animal Science, 94, 125-125. doi:10.2527/msasas2016-265
Keywords: 25Ohd(3); Sow; Vitamin D; Agriculture